Measurement of Phonation Threshold Power in Normal and Disordered Voice Production - Zhuang, Peiyun; Swinarska, Joanna T.; Robieux, Camille F.; Hoffman, Matthew R.; Lin, Shengzhi; Jiang, Jack J. (Annals of otology, rhinology & laryngology, 2013)
Objectives: Phonation threshold pressure (PTP) and phonation threshold flow (PTF) are useful aerodynamic parameters, but each is sensitive to different disorders. A single comprehensive aerodynamic parameter sensitive to a variety of disorders might be beneficial in quantitative voice assessment. We performed the first study of phonation threshold power (PTW) in human subjects. Methods: PTP and PTF were measured in 100 normal subjects, 19 subjects with vocal fold immobility, and 94 subjects with a benign mass lesion. PTW was calculated from these two parameters. In 41 subjects with a polyp, measurements were obtained before and after excision. Receiver operating characteristic (ROC) analysis was used to determine the ability of the three parameters to distinguish between controls and disordered groups. Results: The PTW (p < 0.001), PTP (p < 0.001), and PTF (p < 0.001) were different among the three groups. All parameters decreased after polyp excision. PTW had the highest area under the ROC curve for all analyses. Conclusions: PTW is sensitive to the presence of mass lesions and vocal fold mobility disorders. Additionally, changes in PTW can be observed after excision of mass lesions. PTW could be a useful parameter to describe the aerodynamic inputs to voice production.